HUBUNGAN FAKTOR BIOLOGIS DAN PSIKOLOGIS DENGAN PERILAKU SEKSUAL PADA WANITA MENOPAUSE DI KECAMATAN LIMO DEPOK TAHUN 2011 - Anni Suciawati (Universitas Nasional, 2017)
While psychological distress among old women has brought with it more negative impact than those of men in Europe and the U.S., there is still a question whether such impacts also influence the sexual behavior on the part of women. This study is an attempt to explore the issue, focusing on the correlation between both psychological and biological factors and sexual behavior. The study takes the case of some old women in the monopouse stage, at the sub-district of LIMO, Depok, West Java. Method of the study employs quantitative research with cross-sectional study, using purposive sampling technique. The study was conducted during Nov – Dec 2012. The finding of the study reveals that there a positive correlation between the variables under study.